PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L) DENGAN PEMBERIAN ABU JANJANG KELAPA SAWIT DAN PUPUK NPK PADA MEDIUM GAMBUT - Geovani Restu Buwono; Erlida ' Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aimed to determine the effect of interaction award palm bunch ash and fertilizers NPK, as well as getting the best treatment dose to the growth of cocoa seedlings in peat medium. The study conducted an experiment using a completely randomized design (CRD) factorial with two factors and three replications. The first factor dose palm bunch ash (0, 28,125, 56,25, 112,5 g/polybeg), while the second factor is the dose of fertilizer NPK (3,75, 7,5 g/polybeg). The result showed that the oil palm bunch ash and fertilizer NPK significantly effect the number of leaves, leaf area, the ratio of the canopy and root dry weight of cacao seeds, but the effect was not significant on seedling height and stem diameter. Award bunch ash palm and NPK can enhance the growth of cocoa seedlings. Oil palm bunch ash 112,5 g/polybag with fertilizer NPK 7,5 g/polybag is the best dose. Keywords : Oil palm bunch ash, NPK fertilizers and plant growth.